Estudio de factibilidad para la creación de un vivero agroforestal de plantas en extinción. Sector San Felipe, cantón Mocache. Año 2014 - Camacho Reina, Consuelo Grimanesa (2015)
The project called FEASIBILITY STUDY FOR THE ESTABLISHMENT OF A PLANT NURSERY AGROFORESTAL in extinction. SECTOR SAN FELIPE, CANTON Mocache. YEAR 2014, I present positive results of project implementation, the same as shown in the market survey of the sector to the inhabitants of the Canton San Felipe Mocache. The project is proposed in this paper presents an initiative, while ensuring the collective rights of the citizens, conservation and environmental management aims to offer an alternative solution to reverse the serious environmental impacts that occur as result of pollution from the indiscriminate felling of trees, Ecuador is recognized as a country with a large forest potential…..